FLEKSIBILITAS MAHASISWA UNIVERSITAS UDAYANA YANG BERLATIH TAI CHI LEBIH BAIK DARIPADA YANG TIDAK BERLATIH TAI CHI - Pulcheria, Meryl; Muliarta, I Made (E-Jurnal Medika Udayana; Vol 5 No 6 (2016): E-jurnal medika udayana, 2016)
Stretching can improve flexibility, allow a group or one joint to perform movements efficiently, also make important role in preventing injuries and poor posture improvement. Tai Chi is a low impact low intensity dynamic stretch which can be selected as an exercise to improve flexibility. This study is analytic survey study with cross sectional approach on 30 female students to compare Udayana University students flexibility, with 15 female students regularly practice Tai Chi and 15 female students do not practice Tai Chi. Flexibility is measured by Takei Flexion-A sit and reach test. Mean age of Tai Chi group were 21±1,41 years and mean age of non Tai Chi group were 21±1,36 years. Mean body mass index were 21,37±1,85 dan 21,65±2,97 respectively on Tai Chi and non Tai Chi  groups. Normality test on two groups results were p>0,05 indicated the data distributed normally. Mean flexibility on Tai Chi group was 20,50±2,98cm, and non Tai Chi group was 1,33±7,35cm with mean difference of flexibility was 19,17cm. 95% confidence interval with lower limit of 14,97 and upper limit of 23,36. From independent t-test found significant difference of flexibility between Tai Chi and non Tai Chi group (p=0,000). Tai Chi, including warming up and stretching as its parts, could improve individual flexibility.
Keywords: stretching, flexibility, Tai Chi, sit and reach test